Accounts of whiteness from white university students living in contemporary South Africa - Sly, Daniel (My University, 2019)
Whiteness is a social construction which is continually affected by the context in which it finds itself. Thus, the power and privilege that whiteness holds adapts and evolves over time and over generations. The socio-political history of South Africa has led to the development of a unique society in which the ideology of whiteness has created, and continues to maintain, inequality and systems of power. Whiteness affords the white racial category privilege and power within contemporary South Africa, continuously adapting and enforcing inequality based on racial categories. Therefore, it is useful to study the concept of whiteness in contemporary South Africa in order to gain a greater understanding and awareness of the manner in which whiteness functions as well as to discover whether such concepts may be challenged within contemporary society. The current study utilised focus groups in order to gain accounts of whiteness from white university students who were enrolled in second and third year psychology courses at the University of the Witwatersrand in 2017. Three focus groups were produced and the data collected were analysed using a thematic analysis. Seven themes were produced which were both descriptive as well as interpretive, namely: ‘the anxiety of race talk amongst white people’, ‘universities as unique sites for critical thinking in South Africa’, ‘the myth of the rainbow nation’, ‘the ambivalence of relating to the black Other’, ‘attempts at relieving the burden of being the oppressor’, ‘the recrafting of contemporary whiteness’ and ‘navigating a hostile social terrain within a history of oppression’. Throughout the themes, a deep sense of ambiguity and uncertainty arose in participants with regards to specific places, spaces and contexts within contemporary society. Furthermore, it seems as if white students are attempting to recraft their identities in order to gain a greater sense of belonging. Whiteness seems to be unsettled in a variety of contexts within South Africa as it is challenged more frequently by society and social movements such as #FeesMustFall. The unsettled nature of whiteness within these contexts seems to be a driving force which promotes the need for one to recraft one’s identity. However, this recrafting remains a difficult task in a society where inequality remains so overt and prevalent, continuing to divide the ‘rainbow nation’. Thus, there seems to be further ambiguity with regards to the means by which one may recraft one’s identity within contemporary society.
A research report submitted in partial fulfilment of the degree of Master of Arts in Community-Based Counselling Psychology at the University of the Witwatersrand
Keywords: Privilege (Social psychology); Post-racialism; White people--Race identity